An imaginary without images? Tourists in (and out of) love - Olivier Lazzarotti (Via@)
Six pop songs from the French language repertoire have been selected for the different ways in which they combine tourism and love. This provides the basis for a set of intersecting imaginaries, which in turn informs analysis of the notion of the imaginary per se. Looking beyond images and representations, this imaginary localizes romantic desire, a specific instance of an individual’s relationship with the other. Tourism appears to amplify and sometimes even reveal feelings in a positive or negative way. These songs, which range in focus from order to liberation, are a means of exerting political control over something that, by definition, defies control: the coming together of two human beings.